Tratamento de pneumonia em pacientes hospitalizados 3/4 resultado de um estudo clínico multicêntrico utilizando uma cefalosporina de quarta geração (cefepima) - Medeiros, Eduardo Alexandrino Servolo de [UNIFESP] (1999)
OBJECTIVE: To evaluate efficacy and safety of cefepime in severe pneumonia of hospitalized patients. DESIGN AND PATIENTS: A prospective, multicenter, open trial was performed with 148 patients (62 patients with nosocomial pneumonia; 34 with community-acquired pneumonia and 52 undefined forms). Cefepime was intravenously administered (1,000 to 2,000mg every 12 hours), and doses were adjusted for renal function. The efficacy endpoint was clinical response at 48 hours after completion of therapy. RESULTS: The mean age was 56.4 ± 20,31 years. The most common bacterias isolated from patients with nosocomial pneumonia were: 5 (8.06%) Pseudomonas aeruginosa; 7 (11.29%) Pseudomonas sp.; 6 (9.68%) Klebsiella sp.; 3 (4.84%) E.coli; 2 (3.23%) Acinetobacter baumannii; 3 (4.84%) Staphylococcus aureus; 3 (4.84%) Streptococcus pneumoniae; 5 (8.06%) others. The most common isolates from patients with community-acquired pneumonia were: 2 (5.88%) Streptococcus pneumoniae; 1 (2.94%) S. aureus; 2 (5.88%) P. aeruginosa and 2 (5.88%) K. pneumoniae. Clinical efficacy was demonstrated in 137/148 (92.56%) of the cases since improvement was obtained in 20.27% and healing in 72.29%. Failure of the treatment was observed in 10 patients (6.75%) and one patient the evaluation was not possible. Adverse events were reported for 5/148 patients (3.38%). CONCLUSION: Our data suggest that cefepime was safe and effective for treatment of severe pneumonia in hospitalized patients.